Latencies and amplitude in vestibular evoked myogenic potential in children (Research, Society and Development, 2021)
Objective: The present study has the objective of observing that there are significant differences for the latencies of VEMP between children and adults. Methodology: The study is about a systematic review, with a quantitative nature approach, the descriptors used in the research form: (Child OR Childhood OR Children OR Pediatric) AND (vestibular evoked myogenic potential OR VEMP OR cVEMP OR or VEMP). A selection of two studies and extraction of two data was carried out by only two researchers, where the mean values ​​of latency and amplitude of the VEMP test were obtained from the results obtained from us. Results: We selected studies, a total of 135 individuals for latency studied for a valuation of latencies n1 and p1 of oVEMP, two quais 62 eram children and 73 eram adults, já for valuation of latencies p13 and n23 of cVEMP foram studied 50 people, sendo 25 children and 25 adults. Our procedures were used intensities between 100 to 105 dBnHL, with a frequency of 500Hz in all studies. As the latencies of two components n1 and p1 and amplitude of oVEMP do not have significant differences between entities, especially cVEMP components, it is possible to verify a significant difference not component p13. Conclusion: The values of the latencies of the wave and amplitude component of oVEMP in children do not show significant differences in adults when there is no p13 component of cVEMP that have significant differences by factor of life.